The effect of Piceatannol on Liver function and TGF-β1 expression in Diabetic Rats - Wei, Song; Das, Sreemoy Kanti (Journal of Neonatal Surgery, 2025)
To investigate the effect of piceatannol (PIC) on liver function and the expression of transforming growth factor-β1 (TGF-β1) in diabetic rats, and to provide a basis for future research on the liver-protective effects of PIC in diabetic rats based on TGF-β1. Methods: 40 male healthy SD rats were selected, and 30 of them were used to establish a diabetic nephropathy (DN) model by intraperitoneal injection of streptozotocin. The 30 successfully modeled SD rats were randomly divided into a model group, a PIC-L group (50 mg/kg), and a PIC-H group (100 mg/kg). The remaining 10 rats were normally raised as the control group . All groups started receiving medication after successful modeling. The PIC-L and PIC-H groups were given the corresponding doses of PIC by gavage, while the control group and model group were given 10 ml/kg of saline by gavage. All rats were treated continuously for 4 weeks, once daily. During the medication period, the physiological conditions of the rats were observed. 12 hours after the last administration, the body weight of the rats was measured, urine was collected, and the rats were anesthetized and euthanized. Blood and liver tissues were collected from each group to measure and compare serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AKP),and TGF-β1 lever in liver tissues.Observe the pathological changes in the liver. Results After 28 days of treatment, the levels of ALT, AST, AKP, and TGF-β1 were highest in the model group, followed by the PIC-L group, and lowest in the PIC-H group and the control group. The differences among the four groups were statistically significant (P < 0.05).PIC can significantly improve the pathological changes in the liver of NAFLD rats. Conclusion PIC treatment can improve liver function in diabetic rats, and its liver-protective effects may be mediated by reducing TGF-β1 levels.